Isosteroidal alkaloids of Fritillaria taipaiensis and their implication to Alzheimer's disease: Isolation, structural elucidation and biological activity. (September 2022) - Wang, An-Wen; Liu, Yu-Ming; Zhu, Ming-Ming; Ma, Rui-Xue
Abstract: Four undescribed and five known isosteroidal alkaloids were isolated from the bulbs of Fritillaria taipaiensis and their structures were elucidated on the basis of HR-ESI-MS, 1D and 2D NMR spectroscopic data analyses. The undescribed compounds were designated taipainines A−D. Of these, taipainine D presented a unique structure having the D/E trans (H-13α/H-17β) and E/F cis (β-axial lone pair of the N atom/H-22β) ring junctions. Possible biosynthetic pathway to taipainine D is proposed. Four compounds showed significant BChE inhibitory activities similar or better than the positive control galantamine. In addition, the preliminary structure−activity relationships (SARs) of these isosteroidal alkaloids were also investigated. Graphical abstract: Undescribed isosteroidal alkaloids were isolated from the bulbs of Fritillaria taipaiensis . Some isosteroidal alkaloids exhibited significant ChE inhibitory activities. Image 1 Highlights: Four undescribed isosteroidal alkaloids were isolated from Fritillaria taipaiensis. Taipainine D is unique with D/E trans (H-13α) and E/F cis (H-22β) ring junctions. The biosynthetic pathway of Taipainine D was suggested. Anti-cholinesterase effects of nine isosteroidal alkaloids were reported.